2006
DOI: 10.1002/masy.200690011
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polyelectrolytes in Crystallogenesis of Calcium Carbonate

Abstract: Summary:The effects anionic polyelectrolytes, having various molecular weights and repeating unit structures, on the crystallization of calcium carbonate in supersaturated solutions are studied. The induction times of the crystals grown in the presence of the polymers were optically evaluated; X-ray diffraction and Scanning Electronic Microscopy (SEM) analyses were performed to determine, respectively, their crystalline structures and morphologies. The polyelectrolyte is found to lengthen the induction time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…It has been shown that vaterite is formed on polymeric substrates in the presence of carboxylate groups [8]. Jada and Jradi have studied the influence of anionic polyelectrolites on size and shape of calcite and vaterite crystallisation from supersaturated solutions [20] and various studies have demonstrated that the formation of vaterite is favoured by the presence of amino acids and alcohols. In the presence of the amino acids alanine, glycine, lysine, polyglycine, polymethionine, polylysine [21] and leucine [22] in supersaturated solutions vaterite becomes stable.…”
Section: Vaterite Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that vaterite is formed on polymeric substrates in the presence of carboxylate groups [8]. Jada and Jradi have studied the influence of anionic polyelectrolites on size and shape of calcite and vaterite crystallisation from supersaturated solutions [20] and various studies have demonstrated that the formation of vaterite is favoured by the presence of amino acids and alcohols. In the presence of the amino acids alanine, glycine, lysine, polyglycine, polymethionine, polylysine [21] and leucine [22] in supersaturated solutions vaterite becomes stable.…”
Section: Vaterite Formationmentioning
confidence: 99%
“…Many studies have dealt with crystallization and transformation mechanisms of calcium carbonate polymorphs from aqueous solutions [6][7][8][17][18][19][20][21][22][23][24], with particular interest to the biomineralization process, through which CaCO 3 is naturally formed in vivo. CaCO 3 polymorphism is a very important problem in biomineralization since many organisms are able to exert control over the mineral form and all the three anhydrous crystalline forms have been observed in mollusc shells and fish otoliths macromolecules [9,10].…”
Section: Vaterite Formationmentioning
confidence: 99%
“…In recent works, we investigated the effects of various anionic polyelectrolytes, sodium polystyrene sulfonate (PSS), M w ¼ 10 6 g mol À1 , sodium polyacrylate (PAA), M w ¼ 2.1 Â 10 3 g mol À1 ; sodium polyvinyl sulfonate (PVSA), M w ¼ 30-60 Â 10 6 g mol À1 and sodium poly (maleic acidco-olefin) (PMACO), M w ¼ 12.0 Â 10 3 g mol À1 , on the crystallization of CaCO 3 in supersaturated solutions [27]. We found that the nucleation, the growth, the shape, and the size of the final CaCO 3 particle are function of the monomer structure.…”
Section: Preparation Modes Of Cacomentioning
confidence: 99%
“…Supersaturated solutions for crystal growth experiments were prepared, at ambient temperature, by addition of equal volumes of sodium carbonate (Na 2 CO 3 ) to calcium nitrate (Ca(NO 3 ) 2 Á 4H 2 O) solutions in a water-jacketed Pyrex glass vessel of 300-mL capacity, as described elsewhere [27][28][29]. In each experiment the final concentration of calcium solution, was kept equal to the final concentration of carbonate.…”
Section: Preparation Of Caco 3 Particlesmentioning
confidence: 99%
See 1 more Smart Citation